2022
DOI: 10.1002/cphc.202200440
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Conformational Properties and Role of Hydrogen Bonds in Glycosaminoglycans‐Interleukin8 Complexes in Aqueous Medium by Molecular Dynamics Simulation

Abstract: Atomistic molecular dynamics simulations were performed under ambient conditions to explore the conformational features and binding affinities of hexameric glycosaminoglycans (GAGs) with chemokine Interleukin8 (IL8) in an aqueous medium. We tried to understand the role of hydrogen bonds (HBs) involving conserved water in mediating the interactions. The Luzar‐Chandler model was adopted to study the kinetics of HB breaking and formation concerning different water‐mediated HBs. The conformational flexibilities of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…39 Recently, we showed that the recognition of protein and hexameric CS occurred through water-mediated H-bonds. 35 We adopted the Luzar−Chandler model to study the kinetics of different trapped H-bonds associated with the binding process.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…39 Recently, we showed that the recognition of protein and hexameric CS occurred through water-mediated H-bonds. 35 We adopted the Luzar−Chandler model to study the kinetics of different trapped H-bonds associated with the binding process.…”
Section: Introductionmentioning
confidence: 99%
“…In another study on CS disaccharide torsional space, intra- and intermolecular H-bonds, bridging water molecules, and principal component analysis suggest that the distinct conformational dynamics in different CS disaccharides is the reason for the existence of unique electrostatic surfaces that could be a key for protein recognition . Recently, we showed that the recognition of protein and hexameric CS occurred through water-mediated H-bonds . We adopted the Luzar–Chandler model to study the kinetics of different trapped H-bonds associated with the binding process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation